Correspondance entre le Président du Comité international de la Croix-Rouge et le député de directeur du Bureau Européen de l'ONU . International Committee of the Red Cross to the Deputy Director of the UN European Office - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Leopold Boissier; Comité international de la Croix-Rouge The purpose of this letter is to establish a direct link of communication between these two agencies and to coordinate efforts in order to avoid duplication.